Repurposing Riociguat to Target a Novel Paracrine Nitric Oxide-TRPC6 Pathway to Prevent Podocyte Injury - Daan ‘t Hart (MDPI AG, 2021)
Increased expression and activity of the Ca2+ channel transient receptor potential channel 6 (TRPC6) is associated with focal segmental glomerulosclerosis, but therapeutic strategies to target TRPC6 are currently lacking. Nitric oxide (NO) is crucial for normal glomerular function and plays a protective role in preventing glomerular diseases. We investigated if NO prevents podocyte injury by inhibiting injurious TRPC6-mediated signaling in a soluble guanylate cyclase (sGC)-dependent manner and studied the therapeutic potential of the sGC stimulator Riociguat. Experiments were performed using human glomerular endothelial cells and podocytes. Podocyte injury was induced by Adriamycin incubation for 24 h, with or without the NO-donor S-Nitroso-N-acetyl-DL-penicillamine (SNAP), the sGC stimulator Riociguat or the TRPC6 inhibitor Larixyl Acetate (LA). NO and Riociguat stimulated cGMP synthesis in podocytes, decreased Adriamycin-induced TRPC6 expression, inhibited the Adriamycin-induced TRPC6-mediated Ca2+ influx and reduced podocyte injury. The protective effects of Riociguat and NO were blocked when sGC activity was inhibited with 1H-[1,2,4]Oxadiazolo[4,3-a]quinoxalin-1-one (ODQ) or when TRPC6 activity was inhibited by LA. Our data demonstrate a glomerular (e)NOS-NO-sGC-cGMP-TRPC6 pathway that prevents podocyte injury, which can be translated to future clinical use by, e.g., repurposing the market-approved drug Riociguat.